2017
DOI: 10.3389/fendo.2017.00174
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Nano-vesicles from First Trimester Human Placentae Carry Flt-1 and Levels Are Increased in Severe Preeclampsia

Abstract: Background/objectives: Preeclampsia is a life-threatening hypertensive disease affecting 3-5% of pregnancies. While the pathogenesis of preeclampsia remains unclear, it is known that placenta-derived factors trigger the disease by activating maternal endothelial cells prior to the onset of clinical symptoms. Extracellular vesicles (EVs) of different sizes extruded by the placenta may be one factor. The truncated/secreted form of Flt-1 (sFlt-1) has also been implicated in the pathogenesis of preeclampsia. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…In addition to immunomodulatory factors, vasoactive factors, such as Flt‐1 and endoglin are also present on placental EVs . Furthermore, proteins involved in coagulation/hemostasis, such as tissue factor, are carried by placental EVs .…”
Section: Cargo Of Placental Extracellular Vesiclesmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to immunomodulatory factors, vasoactive factors, such as Flt‐1 and endoglin are also present on placental EVs . Furthermore, proteins involved in coagulation/hemostasis, such as tissue factor, are carried by placental EVs .…”
Section: Cargo Of Placental Extracellular Vesiclesmentioning
confidence: 99%
“…Uptake of EVs allows the delivery of the specific EV‐associated cargos, such as miRNA, into endothelial cells. However, placental EVs may also affect endothelial cell function without being internalized as we and others have shown that EVs derived from preeclamptic placentae carry increased levels of Flt‐1, which can sequester vascular endothelial growth factor and placental growth factor from the micro‐environment …”
Section: Effects Of Placental Extracellular Vesicles On Endothelial Cmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of publications have addressed placental EVs and their potential role in pregnancy and its complications . Several ex vivo (eg, placental perfusion) and in vivo systems have been used as a source of EVs. Placental perfusion is a useful method for obtaining large numbers of EVs directly from the placenta; however, this technique is suitable only for a short period of time (2‐6 hours) after delivery .…”
Section: Discussionmentioning
confidence: 99%